A Mathematical Model of Desiccant Wheel in Desiccant Cooling - Arfidian Rachman (LP2M - Institut Teknologi Padang, 2020)
The desiccant wheel performance of desiccant cooling system components is very important whose function is to regulate air humidity levels as well as to the capability, size and cost of the entire system. Mathematical models for predicting the performance of desiccant wheels in the development of mathematical models is one of the effective methods for analyzing the performance of wheel this moisture-reducing. This mathematical model can also be used in guiding system operation, delivering experimental results and automation in designing this cooling system. The purpose of this paper is to provide an overview of efforts to mathematically model the process of heat transfer and mass transfer that occurs in the moisture-reducing wheel. The desiccant wheel model built here is a gas and solid system including basic principles, heat and mass transfer mechanism and model building. The model is based on ideal assumptions, equations, additional conditions and the method of solution and also the main results. The gas-solid model is a more precise and more complex model than the other models. From these results the evolutionary process of the mathematical model is obtained and the aspects of calculation of pressure loss, air leakage, and optimal rotation speed of the drying wheel / dehumification.